Improving the EMA Binding Test by Using Commercially Available Fluorescent Beads - Glenthøj, Andreas; Sharfo, Alaa; Brieghel, Christian; Nardo-Marino, Amina; Birgens, Henrik; Petersen, Jesper Brix (Frontiers in Physiology, 2020)
Hereditary spherocytosis (HS) is a common anemia caused by germline mutations in red blood cell cytoskeleton proteins. The flow cytometry-based eosin-5’-maleimide (EMA) binding test is most frequently employed for reliable diagnostics but requires a number of age-matched healthy controls, which can be challenging and complicates interlaboratory comparisons. To overcome this limitation, we modified the EMA binding test by replacing healthy controls with commercially available fluorescent beads. Blood samples from 289 individuals with suspected HS were analyzed using the EMA binding test with fluorescent beads and benchmarked against regular EMA binding test using two control samples. Using osmotic gradient ektacytometry as validation, 112 individuals (38.8%) were diagnosed with HS. Performance of the modified EMA binding test was not compromised (accuracy 90.3%) compared to EMA binding test using matched controls (accuracy 88.6%). Based on these findings, we conclude that the modified EMA binding test with fluorescent beads is an attractive alternative, especially in laboratories without easy access to matched controls. Furthermore, as fluorescent beads are stable and easily commutable, they could facilitate both interlaboratory comparisons and quality assessment programs.